Cultural Framing of Risk and Religion within Science Fiction Narratives - Possamai, Adam (Journal for the academic study of religion, 2014)
This article explores some case studies of science fiction narratives concerning human-made worldwide catastrophes (i.e. The Day the Earth Stood Still, I Am Legend, Dawn of the Dead) that have been made and re-made since World War II. It analyses how the notion of risk has changed over this period of time, the degree of human responsibility for these post-World War II catastrophes and how religion, which has not been their root cause, is now being offered as a subtle way out'. The article discovers key differences between narratives on risk in popular culture from the modern and late modern periods.